Paleocene Ostracoda from Nûgssauq, West Greenland. - Szczechura, Janina (Meddelelser om Grønland, 1971)
This paper is the first description of post-Palaeozoic ostracods from Greenland. The material was collected from the Paleocene (Danian) Agatdal Formation on Nugssuaq, West Greenland, a formation which has yielded a huge fauna -over 600 species, mostly gastropods and pelecypods. The ostracod assemblage described comprises 96 specimens belonging to 39 species of 24 genera belonging to the suborders Cladocopina, Platycopina and Podocopina. The genera represented have very varied age ranges; some are known from Paleocene to Recent, others range from Jurassic or Cretaceous up to Recent time. One genus, Sclerochilus, has not previously been found in deposits earlier than Miocene, while another, Orthonotacythere, ranges from Jurassic to Paleocene. None of the species could be assigned with certainty to any hitherto described species and therefore the assemblage is considered to be endemic and consequently does not throw new light on the age of the Agatdal Formation. In the case of four species the material is sufficiently well preserved and plentiful to allow the description of the new species Bairdia agatdalensis, Cushmaniden, rosenkrantzi, Hazelina nova and Loxoconcha groenlandica.